2013
DOI: 10.5901/jesr.2013.v4n3p53
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Teenage Pregnancy on the Educational Attainment of Girls at Chorkor, a Suburb of Accra

Abstract: Recently, the incidence of teenage pregnancy has been very high in Ghana. The study therefore was designed to explore the effects of teenage pregnancy on the educational attainment of the girl-child at Chorkor. A total sample size of fifty-five ( 55) respondents was used for the study. Questionnaire, in-depth interview, focus group discussions and observation were used to collect data for the study. With respect to factors that lead to teenage pregnancy, it was evident that poor parenting, poverty and peer inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
2
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 8 publications
3
53
2
5
Order By: Relevance
“…The findings revealed that was no significant association between the economic status of parents/guardians and teenage pregnancy when the odds ratio was unadjusted. The findings from the study with respect to economic factors contradicted a study by Gyan (2013) that revealed that poverty has a great influence on adolescent pregnancy [24].…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…The findings revealed that was no significant association between the economic status of parents/guardians and teenage pregnancy when the odds ratio was unadjusted. The findings from the study with respect to economic factors contradicted a study by Gyan (2013) that revealed that poverty has a great influence on adolescent pregnancy [24].…”
Section: Discussioncontrasting
confidence: 83%
“…Our findings indicate that household socio-economic status and sex education at a religious level were not statistically significant; it was observed that as household socioeconomic status changes from "Middle" to "High" status, the chances of the teenagers becoming pregnant increases from 2.04 to 2.94 when other covariates were adjusted for in the model. The finding contradicts a study by Gyan (2013) that revealed that poverty has a great influence on adolescent pregnancy [24]. It was clear that teenagers who indicated receiving sex education during their religious activities rather have 2.4 times higher chance of becoming pregnant as compared to those never received sex education at the same level.…”
Section: Discussioncontrasting
confidence: 58%
“…This could be due to lack of school fees and scholastic materials, as well as lack of transport to and from school as similarly observed by Omoro et al (2017). Education plays an important role in empowering teens with information and knowledge about safe sex, as reported in other studies(Cook, 2010; Gyan, 2013; Omoro et al, 2017; Stanger-Hall & Hall, 2011; Westway, Barratt, & Seeley, 2009).…”
Section: Discussionmentioning
confidence: 59%
“…Teenage pregnancy is highly associated with abortions, infant and maternal mortality, high rate of unemployment, school failure and drop-outs and limited future career opportunities. As a result of increased awareness of the socioeconomic consequences of teenage pregnancy, researchers and policy makers have concluded that teenage pregnancy and childbearing is a serious problem (Gebregzabher, Hailu, & Assefa, 2018; Lillian & Mumbango, 2015; Gyan, 2013; Yakubu & Salisu, 2018; Ayanaw Habitu, Yalew, & Azale Bisetegn, 2018; Omoro et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Persalinan pada ibu dibawah usia 20 tahun memiliki kontribusi dalam tingginya angka kematian neonatal, bayi dan balita. Menurut SDKI 2012 angka neonatal, postnatal, bayi dan balita pada ibu yang berusia kurang dari 20 tahun lebih tinggi dibandingkan pada usia 20-39 tahun (Gyan, 2013).…”
Section: Kehamilan Pranikah Remaja DI Kabupatenunclassified